Low-cost, synthetic model for training and simulation of open and semi-open rhinoplasty - Arthur Antunes Coimbra Pinheiro Pacífico; Bárbara Matos de Carvalho Borges; Anna Letícia Silveira Parnaíba; Marco Antônio de Lucena Furtado; Samy Lima Carneiro; Mateus Pinheiro Fernandes Feitosa Arrais; Davi Sousa Garcia (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: Rhinoplasty is indicated for performing aesthetic repairs in the nose, being functional when it also seeks to improve respiratory function. Procedure results are based on improved quality of life and patient satisfaction. It is a complex surgery that requires adequate training. In this sense, several strategies were introduced, such as educational videos, simulations, studies on cadavers and in clinical skills laboratories; however, the basis of training remains the master-apprentice relationship in surgery. Methods: The base materials used in the construction of the model were: hot glue, basin, water, detergent, epoxy putty, spatulas for crafts, nose mold, suture threads, white acetic silicone, disposable cup and spoon and coloring agents. Results: The resulting low-cost model has remarkable similarity with the external appearance and with the cartilages of the nose, allowing easy identification and handling of each structure. Allows good simulation of some steps of the open and semi-open techniques of rhinoplasty. Conclusion: The new synthetic model developed avoids ethical and legal questions that alternative methods such as animals and fresh cadavers raise. Although it requires skill for its manufacture, it has characteristics such as low cost, which favor its dissemination among medical schools. The exposed model can positively impact the learning process of rhinoplasty, revealing itself as an accessible and helpful tool for training in various stages of the technique of this complex surgery.